Reviews (Blackfriars, 1934)
Le Thomisme et la Critique de la Connaissance. By Régis Jolivet. Individuum und Gemeinschaft beim hl. Thomas von Aquin. By Edelbert Kurz, O.F.M. De Sacra Liturgoa Universim. By C. Callewaert, J.C.D. The Liturgical Altar. By Geoffrey Webb. Directions for the use of Altar Societies and Architects. Ida Elisabeth. By Sigrid Undset. Translated from the Nor wegian by Arthur G. Chater. G. La Recle de Saint Benoit. (Abbaye de hlaredsous; 9 frs.)